The SIAR Book (Interactive Science with Augmented Reality) for Enhancing Science Process Skills of Students in Indonesia - Maisarah, Maisarah; Prasetya, Cyndi; Lailissa'adah, Lailissa'adah; Nazwa, Farah; Ain, Imelja Nurul (Universitas Pendidikan Indonesia, 2024)
The science process skills of elementary school students in Langsa city are still relatively low, despite these skills being a crucial element in science education based on the Merdeka curriculum. Additionally, teachers have reported several challenges, including the presence of abstract science material, textbooks that use two-dimensional visualizations, and the inability to practice all science concepts. This research developed the SIAR book (Interactive Science with Augmented Reality) to enhance science process skills. The study produced an elementary school science book that includes observational activities and integrates augmented reality (AR) to present more concrete three-dimensional visualizations. The objectives of this study were to create a valid and effective SIAR book product for improving science process skills. This research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) for development. Participants included three expert validators and 100 elementary school students. The results indicated that: (1) the SIAR book is highly valid for improving science process skills, with a validity score of 96.11%; (2) the SIAR book is effective in enhancing science process skills, achieving a gain score of 0.76, which falls within the high criteria. Based on these findings, it can be concluded that a book integrated with AR can assist students in improving their science process skills. As science process skills improve, students' understanding of science also increases. Therefore, science education in schools should leverage digital technology, as it meets students' needs and facilitates the learning process in science.